Analysis of interaction between nutritional and developmental instability in mediaeval population in Wrocław - Gawlikowska-Sroka, Aleksandra; Dąbrowski, Paweł; Szczurowski, Jacek; Staniowski, Tomasz (Anthropological Review, 2013)
In this paper, we test the hypothesis that indices of nutritional stress from enamel hypoplasia increase the incidence of indicators of developmental instability in fluctuating asymmetry, even in high social status individuals. The studied material consisted of a medieval sample of 58 skulls from the Wrocław area. Radiographs were taken in postero-anterior (P-A) and base projections. Images were scanned and calibrated by means of MicroStation 95 Academic Edition software, and measurements of the skull images were used to estimate fluctuating asymmetry. The presence of hypoplasia and caries was assessed using standard anthropological methods and all data was statistically analysed. The highest levels of fluctuating asymmetry were observed in the skull base region. Hypoplasia was observed in 40% and caries in 55.5%.Differences were noted in the level of fluctuating asymmetry in relationship to the presence or absence of hypoplasia, where a higher level predisposes individuals to enamel hypoplasia and a decline in buffering capacity, regardless of their socio-economic status.